Cheesecake Customized Using Juice and By-Products from Prickly Pears: A Case Study of Recycling and Environmental Impact Evaluation - Alessia Le Rose; Olimpia Panza; Dario Caro; Amalia Conte; Matteo Alessandro Del Nobile (Foods)
Due to the increasing concern about the negative impact of the modern food system and the need to design foods to improve their healthiness and sustainability, in the current study, a fortified cheesecake was developed by using juice, peels, and pomace from prickly pears, which are fruit by-products rich in active compounds. After proper dehydration and being ground to produce a fine powder, some traditional ingredients were substituted with fruit juice and by-products. The water content loss during dehydration and the energy consumed per g of dehydrated by-product were assessed using a proper mathematical approach. A sensory evaluation was carried out using a panel test, thus verifying that the new dessert made with prickly pears was comparable to the traditional one; both recorded high scores of acceptability (sensory score ranged between 8 and 9). The centesimal composition of the two cheesecakes also demonstrated that the ingredient substitution did not affect the energetic value of the final product (290 vs. 248 kcal/100 g); on the contrary, it promoted an increase in carbohydrates (27.38 vs. 26.26 g/100 g), lipids (16.98 vs. 12.94 g/100 g), and total fibers (5.7 vs. 4.2 g/100 g). To demonstrate that the recycling of by-products from prickly pears could represent an advantage from an environmental point of view, a full Life Cycle Assessment (LCA) was carried out. In relation to this, three environmental impact categories, such as Global Warming Potential, Acidification and Eutrophication, which are associated with three different biowaste treatment options—such as composting, landfilling, and recycling—were assessed. The results from the LCA highlighted that recycling always emerged as the most sustainable biowaste management option. For all environmental impact categories analyzed, recycling resulted in an overall environmental saving (−7.63 kgCO2eq/kg biowaste; −0.116 kgSO2eq/kg biowaste; and −0.055 kgPO43−eq/kg biowaste). In addition, the comparison between the traditional cheesecake and the fortified one, in terms of impacts per kg of cheesecake, demonstrated that replacing food items with recycled biowaste may result in a general reduction in emissions and resources. Therefore, this case study represents a valid example of zero-waste production, offering a concrete suggestion as to how processed foods can be redesigned to make them healthier from a more sustainable perspective.